The combination of perception of other individuals and exogenous manipulation of arousal enhances social facilitation as an aftereffect: re-examination of Zajonc’s drive theory - Ukezono, Masatoshi; Nakashima, Satoshi F.; Sudo, Ryunosuke; Yamazaki, Akira; Takano, Yuji (Frontiers in Psychology, 2015)
Zajonc’s drive theory postulated that arousal enhanced through the perception of the presence of other individuals plays a crucial role in social facilitation (Zajonc, 1965). Here, we conducted two experiments to examine whether the elevation of arousal through a stepping exercise as an exogenous factor in front of others causes social facilitation of a cognitive task in a condition where the presence of others did not elevate the arousal level. In experiment 1, as an “aftereffect of social stimulus”, we manipulated the presence or absence of others and arousal enhancement before participants conducted the primary cognitive task. The results showed that the strongest social facilitation was induced by the combination of the perception of others and arousal enhancement. In experiment 2, we manipulated these factors by adding the presence of another person during the task. The results showed that the effect of the presence of the other during the primary task is enough on its own to produce facilitation of task performance regardless of arousal enhancement as an aftereffect of social stimulus. Our study therefore extends the framework of Zajonc’s drive theory in that the combination of the perception of others and enhanced arousal as an “aftereffect” was found to induce social facilitation especially when participants did not experience the presence of other while conducting primary task.